Basic Profile of Early Childbirth in the Republic of Congo - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of early childbirth are high in the Republic of Congo. The share of women ages 18-22 who had a child before 18 is 31.8 percent, and it has decreased only slightly over time. The share of girls with a child before the age of 15 has also decreased slightly. Early childbirth is associated with lower wealth, lower education levels, and employment without cash earnings. These are however only correlations, not necessarily causal effects. In order to design programs and policies to reduce the prevalence of early childbirth, information is needed on its trend over time, where it is most prevalent in a country, and what the characteristics of girls giving birth early are.